2017
DOI: 10.17116/terarkh201789678-83
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of different celecoxib regimens in patients with active axial spondyloarthritis: Results of the 4-week pilot open-label comparative single-center study «AIM»

Abstract: Different regimens using nonsteroidal anti-inflammatory drugs demonstrated their feasibility, efficiency, and safety in AxSpA patients with high disease activity. The continuous use of celecoxib showed a gradual decrease in clinical and laboratory activity. The de-escalation dose of celecoxib achieved a permanent laboratory activity reduction and pain relief when using 600 mg celecoxib, and after reducing its dose to 200 mg/day, there was a decrease in laboratory disease activity without substantially changing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Thus, 32 references were evaluated by reading their complete texts. At this stage, 29 references were excluded: 18 according to the type of study [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (noncomparative studies; observational, single-arm studies; systematic reviews without meta-analysis or with overlapping studies; language other than Portuguese, English, or Spanish; and abstracts); eight according to the type of intervention [27][28][29][30][31][32][33][34] (drugs not registered in the country and anti-inflammatory agents other than NSAIDs); two according to the type of outcome [35,36] (indirect/incomplete analyses, ineligible outcome); and one according to the type of population [37] (not AS and not spondyloarthritis). Thus, three RCTs [38][39][40] were considered eligible.…”
Section: References Eligible For Meta-analysesmentioning
confidence: 99%
“…Thus, 32 references were evaluated by reading their complete texts. At this stage, 29 references were excluded: 18 according to the type of study [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (noncomparative studies; observational, single-arm studies; systematic reviews without meta-analysis or with overlapping studies; language other than Portuguese, English, or Spanish; and abstracts); eight according to the type of intervention [27][28][29][30][31][32][33][34] (drugs not registered in the country and anti-inflammatory agents other than NSAIDs); two according to the type of outcome [35,36] (indirect/incomplete analyses, ineligible outcome); and one according to the type of population [37] (not AS and not spondyloarthritis). Thus, three RCTs [38][39][40] were considered eligible.…”
Section: References Eligible For Meta-analysesmentioning
confidence: 99%
“…81 Eight studies on NSAIDs were included, of which two non-inferiority RCTs in r-axSpA, one at low and one at unclear RoB (Table 2). [82][83][84][85][86][87][88][89] The first study demonstrated non-inferiority of two doses of etoricoxib (60 and 90 mg daily) versus naproxen 1000 mg daily on VAS spinal pain (SMD between etoricoxib 60 mg and 90 mg with naproxen: 0.07 (−0.24, 0.10) and 0.03 (−0.19, 0.26). 82 The second RCT demonstrated the non-inferiority of two doses of celecoxib (400 mg and 200 mg) versus diclofenac 150 mg daily in VAS global pain (SMD not possible to calculate).…”
Section: Efficacy Of Pharmacological Interventions: Non Tsdmardsmentioning
confidence: 99%